Palm Oil Clinker: A Potential Partial Sand Replacement In Brick Production - Khairunisa, Muthusamy; M. F. S., Ali; M. N. A. A. , Zawawi; N., Nordin; Sharifah Maszura, Syed Mohsin; Nur Farhayu, Ariffin (Penerbit UMP, 2017)
The present research stems out from the environmental problem posed by dumping of palm oil clinker, a by-product of palm oil industry and excessive sand mining issues. Thus, experimental work has been conducted to investigate the effect of palm oil clinker content as partial sand replacement on the properties of brick. A total of five mixes containing various percentage of palm oil clinker, which are 0%, 10%, 20%, 30% and 40% have been prepared. All specimens were water cured until the testing date. The compressive strength test, flexural strength test and water absorption test was conducted at 7 and 28 days. The findings show that incorporation of 10% palm oil clinker contributes towards densification of the mix which enhances both compressive strength and flexural strength performance of the brick. The water absorption of the brick increases slightly when palm oil clinker is integrated as partial sand replacement. On overall, the brick produced using palm oil clinker as partial sand replacement can be used for non load bearing application.